Intake, eating pattern, nutrients digestibility and growth of Tharparkar heifers fed inorganic and organically produced feeds - SINGH, SULTAN; KUNDU, S S; NAG, S K; SURESH, G; MAITY, S B (The Indian Journal of Animal Sciences, 2012)
A feeding trial was conducted for 3 months on 12 Tharparkar heifers equally distributed between inorganic (G ) and organic dietary groups (G ), (n,6) in each with mean body weight of 216.0±8.30 and 218.6±7.09 kg were offered ad lib. sorghum hay (cv PC 6) grown under inorganic and organic agronomic practices, respectively. Barley grain/oat grown inorganically and organically was used as energy sources in concentrate mixture with linseed cake as protein source to determine the intake, eating pattern, nutrients utilization, nitrogen balance and growth rate under both the feeding regimes. DMI (kg/d) was comparable in animals fed inorganic (G 2 1 ) and organically produced diets (G ). OM and hemicellulose digestibility was significantly higher in animals of G 2 than G . The digestibility of fiber fractions was 3– 3.5 units more in animals of G 2 than G 1 1 . N retention was more animals fed organic diet (6.70) than inorganically produced diet (2.46%). Heifers fed organic fodder consumed more at early 2 and 4 h feeding than animals fed inorganic fodder and feed, however at later stages of eating animals offered inorganic fodder/feed, consumed relatively more. Growth rate (g/d) was identical in heifers of G 1 and G dietary groups. Results revealed that nutrients digestibility and nitrogen balance is higher in animals fed organically grown fodder and feeds. 2 2 1